The Development of Surga Beach Tourism Potential in East Lombok Regency - Emra, Auliana; Amri, Zul; Dewata, Indang (Sumatra Journal of Disaster, Geography and Geography Education, 2018)
This research attempted to study about the development of tourism potential in East Lombok Regency (object: Surga Beach). It adopted a descriptive qualitative research design. The data was in the form of qualitative data and collected through interview. The result explained about the development of the potential and its inhibiting factors in East Lombok Regency. With surga Beach’s contribution to Locally-Generated Revenue (PAD) and better regional autonomy, East Lombok still had many problems in developing the tourism potential. The development is hoped to give a positive impact to tourism in Indonesia in general and tourism in Lombok in particular that government, local people and private parties should pay greater attention to it.